2012
DOI: 10.14393/hygeia817905
|View full text |Cite
|
Sign up to set email alerts
|

Análise Espacial Da Prematuridade, Baixo Peso Ao Nascer E Óbitos Infantis Em Uberlândia-Mg

Abstract: As mortes consideradas evitáveis são as que poderiam ser prevenidas, total ou parcialmente, por ações efetivas dos serviços de saúde, que estejam acessíveis em um determinado local e época. Este texto analisa espacialmente a deficiência de peso ao nascer, a prematuridade e o coeficiente dos óbitos infantis, em Uberlândia-MG, a partir do georreferenciamento dos dados do Sistema de Mortalidade Infantil - SIM. Foram classificados e analisados os bairros de maior ocorrência de internação e também, sistematizado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…The odds of a baby born prematurely were 2.5 times higher among women with a partner than those without a partner. This finding differs from a Brazilian case-control study, which found that the absence of a stable partner increased by 7.92% the chances of premature birth 46 . In addition, the lack of a partner increases the difficulties and responsibilities 47 .…”
Section: Discussioncontrasting
confidence: 99%
“…The odds of a baby born prematurely were 2.5 times higher among women with a partner than those without a partner. This finding differs from a Brazilian case-control study, which found that the absence of a stable partner increased by 7.92% the chances of premature birth 46 . In addition, the lack of a partner increases the difficulties and responsibilities 47 .…”
Section: Discussioncontrasting
confidence: 99%